The Role of Artificial Intelligence in Enhancing Critical Thinking Skills of Educational Technology Students: The Moderating Influence of Digital Literacy and Usage Regulation - Riski Dwi Andrian; Yessi Mey Widianti; Desmita Ayu Rachma Wati (Universitas Negeri Surabaya, 2025)
This research examines the role of artificial intelligence (AI) in developing the critical thinking skills of students in the Educational Technology program. In the digital age, critical thinking is essential for objectively evaluating information, solving problems, and making rational decisions. However, much of the learning in higher education is still one-way, limiting the development of these skills. Thru literature review, this study examines the relationship between AI usage and critical thinking skills, specifically in the context of higher education. The results show that AI can trigger students' analysis, evaluation, and reflection processes thru adaptive and interactive learning, with immediate feedback and personalized learning. Nevertheless, the successful implementation of AI depends on students' digital literacy, pedagogical design, and policies regarding AI use on campus. Other challenges such as technology dependence, algorithmic bias, and faculty readiness also need to be considered. A key novelty of this study is the identification of cognitive off-loading as a central risk, highlighting that AI’s impact is not merely supportive but can potentially weaken students’ independent reasoning if not regulated properly. This novelty underscores the urgent need for clear usage guidelines to ensure that AI strengthens rather than replaces students’ critical thinking processes. Overall, this research indicates that integrating AI into learning can enhance students' critical thinking abilities, provided it is used to support independent thinking and reflection, with a planned and ethical approach, making AI an intellectual partner in active, creative, and meaningful learning.